Oral History as a tool for the study of life, the Maria de Lourdes case/A História Oral como ferramenta para o estudo de vida, o caso Maria de Lourdes - Camillo Gustavo Xavier Costa; Jorge Douglas Vieira Cabral Souza (Universidade Estadual de Alagoas, 2020)
This work aims to report our experience with Oral History, developed in the Special Topic Course in History Teaching of the Master's program Prof.História at UFS. This experience had as its culminating point a research practiced in the Florestan Fernandes Settlement, located in Canindé de São Francisco-SE, for that purpose we made use of the Oral History Methodology, which offers innumerable possibilities, among them the one of giving voice to "little men", so that from their experiences and worldviews, we can have an unofficial understanding of the most varied events. It is worth highlighting the importance of our interviewee, Mrs. Maria de Lourdes, whose rich testimony contributed a lot to the elucidation of different issues. It is worth noting that the article had as its guiding concepts the aforementioned Oral History, as well as Memory, Social Identity and Places of Memory.